2014
DOI: 10.1177/0022022114537703
|View full text |Cite
|
Sign up to set email alerts
|

Gross and Fine Motor Differences Between Cameroonian and German Children Aged 3 to 40 Months

Abstract: Based on longitudinal data, this study compared the gross and fine motor development of Cameroonian Nso children and German middle-class children with assessments at 3, 6, 9, and 40 months. A total of 345 infants from Cameroon (n = 73) and Germany (n = 272) were recruited for this study. Complete longitudinal gross and fine motor assessments based on the Bayley Scales of Infant Development III were available for subsamples of the originally recruited children. As the results show, the predictability of the 40-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…[47][48][49][50] The test item with the greatest difference was 'sitting without support', which was passed by 94.5% of Cameroonian infants but only by 6.8% of the German children at 3 months. [47][48][49][50] The test item with the greatest difference was 'sitting without support', which was passed by 94.5% of Cameroonian infants but only by 6.8% of the German children at 3 months.…”
Section: Sub-saharan Africa (Cameroon Nso) Versus Europe (Germany)mentioning
confidence: 99%
See 3 more Smart Citations
“…[47][48][49][50] The test item with the greatest difference was 'sitting without support', which was passed by 94.5% of Cameroonian infants but only by 6.8% of the German children at 3 months. [47][48][49][50] The test item with the greatest difference was 'sitting without support', which was passed by 94.5% of Cameroonian infants but only by 6.8% of the German children at 3 months.…”
Section: Sub-saharan Africa (Cameroon Nso) Versus Europe (Germany)mentioning
confidence: 99%
“…The applicability and/or validity of the BSITD-3 were studied in African, [46][47][48][49][50] Asian, 51,52 Australian, 53,54 and European infants. 34,[47][48][49][50]55,56 A total of 3467 infants, age range 14 days to 42 months, participated in the eight studies.…”
Section: Bsitd-3mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Lohaus, Lamm, Keller et al . () found that German children tended to get a higher score than Cameroonian children on Bayley‐III items involving stairs, manipulation of objects and use of tools such as scissors or pens, most likely because these objects were not part of the natural environment of Cameroonian children.…”
Section: Introductionmentioning
confidence: 99%